A review of the biology of Neochalcis Kirby (Hymenoptera, Chalcididae) with a new host and biological data for N. breviceps (Masi). Issue 27 (18th July 2021) - Abhisree, P.; Ranjith, A. P.; Nasser, M.; Delvare, Gérard
ABSTRACT: The present study reports a new host association of Neochalcis Kirby, N. breviceps Masi reared from an apid bee, Braunsapis breviceps (Cockerell). This is the first report of hymenopteran parasitism of Neochalcis from the Oriental region. Association of parasitic Hymenoptera with Drynaria quercifolia (L.) J. Sm. (Polypodiaceae) and the biology of Neochalcis are briefly commented.